Psychosocial Risk and Protective Factors Related to Psychological Problems among Widows from the Civil Unrest in Southern Thailand - Prohmpetch, Wattana; Tongkumchum, Phattrawan; McNeil, Rhysa (The Journal of Behavioral Science, 2024)
Psychosocial factors have a high influence on both the risk and protective factors leading to psychological problems such as post-traumatic stress disorder (PTSD), complicated grief (CG), and depression in those who have lost loved ones in violent situations. This study aimed to develop and validate a model of the relationships among psychosocial risk and protective factors on psychological problems of bereaved widows from the civil unrest in the southernmost provinces of Thailand. This cross-sectional study involved 350 widows who were asked to join voluntarily prior to participating in this research. The psychologist-volunteers conducted preliminary interviews and assessment using questionnaires between September 2019 and February 2020 in the three provinces of Thailand, Pattani, Yala, and Narathiwat. Data were analyzed using structural equation modeling. The results indicated that the psychosocial risk factors (interpersonal conflicts, family problems, and external stressors) showed high positive effects, while the protective factors (resilience, self-efficacy, and quality of life) revealed low positive effects on psychological problems ( = 14.92, df=13, p = .31, RMSEA = .02, SRMR = .02, CFI = 1.00, TLI = 1.00). Both psychosocial risk and protective factors could explain as 61% of the variance of the psychological problems. Due to the high impact of the psychological problems on both PTSD and CG, protective factors may not be able to function, while risk factors had a high impact to develop psychological problems. Therefore, in order to reduce PTSD and CG among widows, risk factors should be considered to guide the development of psychosocial support programs. However, protective factors should be further studied.